Pharmacological strategies to reduce anthracycline-associated cardiotoxicity in cancer patients. (22nd September 2022) - Stansfeld, Anna; Radia, Utsav; Goggin, Caitriona; Mahalingam, Preethika; Benson, Charlotte; Napolitano, Andrea; Jones, Robin L; Rosen, Stuart D; Karavasilis, Vasilios
ABSTRACT: Introduction: Anthracycline chemotherapeutic agents are widely used in the treatment of hematological and solid tumors, working principally through DNA intercalation and topoisomerase II inhibition. However, they are also well known to have cardiotoxic sequelae, commonly denoted as a reduction in ejection fraction. Drug-associated cardiotoxicity remains a significant limiting factor in the use of anthracyclines. Areas covered: In this review, we explore the potential mechanisms of anthracycline-associated cardiotoxicity, identifying high-risk cohorts and approaches to cardiovascular monitoring. The mechanisms through which cardiotoxicity occurs are complex and diverse, ultimately leading to increased oxidative stress, mitochondrial dysfunction, and subsequent cellular apoptosis. Many of the cardiotoxic effects of anthracyclines exhibit a dose-dependent cumulative relationship and are more apparent in patients with previously existing cardiovascular risk factors. Long-term cardiovascular monitoring and optimization of risk factors, prior to commencing treatment as well as beyond the time of treatment, is therefore essential. Expert opinion: We discuss some of the pharmacological strategies proposed to mitigate anthracycline-associated cardiotoxicity as well as prevention strategies to reduce the burden of coexisting cardiovascular risk factors. We highlight methods of early detection of patient cohorts who are at increased risk of developing anthracycline-associated cardiotoxicity and identify potential avenues for further research.